THE ROLE OF DIGITAL INNOVATION IN ENHANCING FIRM VALUE: A STUDY OF INDONESIAN STATE-OWNED BANKS - Hasri Nirmala Budiarti; Ilma Aini Imania (KOMITMEN: Jurnal Ilmiah Manajemen, 2025)
This study aims to examine the effect of digital innovation on firm value as measured by four indicators: Price to Book Value (PBV), Price Earnings Ratio (PER), Earnings Per Share (EPS), and Tobin’s Q. The Resource-Based View (RBV) Theory is used as the theoretical framework to understand how distribution channels such as ATMs, internet banking, and mobile banking services function as strategic resources in enhancing firm value. This study employs a quantitative approach using a census method, with the entire population of four state-owned banks serving as the sample. Secondary data was obtained from the banks’ annual reports for the period 2019-2024. The analysis technique used is simple linear regression, with SPSS 26. The research results indicate that digital innovation influences PBV and Tobin’s Q, but does not Influence PER and EPS. These findings support the notion that digital innovation, as a strategic asset within the RBV framework, can drive increases in firm value. However, this effect is not yet uniform across all financial indicators.